Investigating risk-taking and executive functioning as predictors of driving performances and habits: a large-scale population study with on-road evaluation - Le Denmat, Pierre; Grisetto, Fanny; Delevoye-Turrell, Yvonne N.; Vantrepotte, Quentin; Davin, Tanguy; Dinca, Andreea; Desenclos-El Ghoulti, Isabell; Roger, Clémence (Frontiers in Psychology, 2023)
Maladaptive behavior often results from poor decision-making and by extension poor control over decisions. Since maladaptive behavior in driving, such as excessive speed, can lead to dramatic consequences, identifying its causes is of particular concern. The present study investigated how risktaking and executive functioning are related to driving performance and habits among the general population. Five hundred and eighty-nine participants completed an on-road driving session with a professional driving instructor and a self-reported checklist of difficult driving situations typically avoided. Additionally, participants completed a set of experimental tasks assessing risk-taking tendencies, reactive adaptive mechanisms, and two distinct forms of inhibition: interference control and response inhibition. The results of the present study revealed several significant findings. Firstly, poor driving performance was associated with a high avoidance of challenging driving situations. Secondly, neither form of inhibition studied (interference control or response inhibition) predicted driving performance. Thirdly, while greater involvement in reactive adaptive mechanisms did not predict better on-road performance, it was associated with a reduced tendency to avoid difficult situations. Surprisingly, a higher propensity for risk-taking predicted better on-road performance. Overall, these results underline limited links between executive functioning and driving performance while highlighting a potentially more complex relationship between risk-taking tendencies and driving. Executive functioning, however, appears to be linked to driving habits.